Yves Gingras, Science and Religion: An Impossible Dialogue. (25th January 2019) - Lataster, Raphael
Abstract : Yves Gingras, Science and Religion: An Impossible Dialogue. Cambridge & Boston: Polity, 2017, pp. x + 249, ISBN: 978-1-5095-1893-7.